PENERAPAN MODEL PROJECT BASED LEARNING (PJBL) UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS IV SEKOLAH DASAR - Meriantama Ginanjar Saputra; Fida Rahmantika Hadi; Laila Riyanasari (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2023)
This research was motivated by the results of students' cognitive ability tests in grade 4 science subjects at SDN Nongkodono Ponorogo which were at a low level. Through the pre-cycle stage, the result was that 60% of the cognitive abilities of grade 4 students had test scores that had not reached the minimum completeness criteria. The purpose of this research is to improve science learning outcomes with the help of project-based learning models. The research approach used was Classroom Action Research (CAR) by adopting the Kemmis and Mc Taggart models. Data collection techniques used are observations and tests. While the data analysis used descriptive qualitative and descriptive comparative. The research implementation lasted for 2 cycles with two meetings in each cycle. Based on the results of research that has been carried out in cycle I, the percentage of completeness has increased by 30% to 70%. While in cycle II the percentage of completeness increased by 30% to 100%. Therefore it can be concluded that the application of the Project Based Learning (PjBL) model can improve science learning outcomes in grade 4 elementary school students.